The interaction of a self-assembled nanoparticle and a lipid membrane: Binding, disassembly and re-distribution - Lilia Milanesi; Salvador Tomas (Heliyon)
Here we report a detailed study of the interactions of nanoparticles, formed by the self-assembly of cholesterol-containing porphyrins, with lipid membranes. We show that the interaction is a two-step process: first, the docking and fusion, then, the redistribution of the building blocks of the self-assembled nanoparticles (SANs henceforth). Analysis of the binding and structural data is consistent with the docking step being driven by a multivalence cooperative effect and with the formation of SAN aggregates on the membrane, whilst the solubility of the cholesterol anchor in the membrane is key to both the fusion and redistribution of the SANs building blocks. The tendency of the SAN to aggregate in the membrane helps explain the photosensitizer properties of the SANs, essential to their anti-microbial activity. The solubility of the cholesteryl anchors drives fusion to the membrane and de-assembly of the SAN, explaining the capability of the SANs to deliver therapeutic cargos at the lipid interface. The subsequent redistribution of the SANs building blocks offer a plausible pathway to body clearance that is not immediately available to hard nanoparticles. These properties, and the modularity of the synthesis, point to the SANs being an excellent platform for the development of nanomedicines. An unexpected consequence of unraveling the mechanism of membrane interaction of these SANs is that it allows us to derive a value of the free energy of binding of cholesterol (the membrane anchor of the SAN building blocks) to a lipid membrane, that is consistent with the literature values. This is an additional property that can be exploited to determine the affinity of a variety of membrane anchors to membranes of various compositions.